Subtle manipulation of egg sex ratio in birds. - Arnold, Kathryn E (2003)
Mothers are predicted to overproduce male or female eggs when the relative fitness gains from one sex are higher and outweigh the costs of manipulation. However, in birds such biases are often difficult to distinguish from differential embryo or chick mortality. Using a molecular technique to identify the sex of early embryos, we aim to determine the effect of maternal nutrition on zebra finch (Taeniopygia guttata) egg sex ratios after 2 days of incubation, which is as close to conception as is currently possible. We found no overall bias in the sex ratio of eggs laid and sex did not differ with relative laying order under any diet regime. However, mothers on a low-quality diet did produce a female bias in small clutches and a slight male bias in large clutches. On a high-quality diet, mothers produced a male bias in small clutches and a female bias in large clutches. Those on a standard diet produced a roughly even sex ratio, irrespective of clutch size. These observed biases in egg sex are partly in line with predictions that, in this species, daughters suffer disproportionately from poor rearing conditions. Thus, when relatively malnourished, mothers should only rear daughters in small broods and vice versa. Sex-ratio patterns in this species therefore appear to be subtle.